2001
DOI: 10.1128/iai.69.2.968-976.2001
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity ofChlamydia trachomatisSerovar LGV but Not E Is Dependent on Host Cell Heparan Sulfate

Abstract: The ability of heparan sulfate, heparin, and other glycosaminoglycans to inhibit the infectivity of Chlamydia trachomatis serovars E and LGV was examined using a simple competitive inhibition assay with three cell types from the human female reproductive tract, including primary human endosalpingeal cells. With the majority of the glycosaminoglycans tested, LGV was more significantly inhibited than serovar E. We have compared chlamydial infectivity between a wild-type Chinese hamster ovary cell line and two gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 50 publications
6
82
0
Order By: Relevance
“…Our study confirmed that following bacterial attachment, typical inclusions formed that were permissive to bacterial growth, resulting in increased infectious progenies in [17][18][19][20][21][22]. Heparin, which forms the majority of GAGs, also plays a critical role in host cells as a receptor for the attachment of the other pathogens such as Bordetella pertussis [35], Hemophilus influenzae [36] or Neisseria gonorrhoeae [37].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our study confirmed that following bacterial attachment, typical inclusions formed that were permissive to bacterial growth, resulting in increased infectious progenies in [17][18][19][20][21][22]. Heparin, which forms the majority of GAGs, also plays a critical role in host cells as a receptor for the attachment of the other pathogens such as Bordetella pertussis [35], Hemophilus influenzae [36] or Neisseria gonorrhoeae [37].…”
Section: Discussionsupporting
confidence: 64%
“…Heparin independent attachment and host invasion has also been described for the C. trachomatis LGV invasive serotype causing a systemic disease, but not for any other serotypes [17][18][19][20][21][22]. This suggests that a heparin-independent attachment mechanism is useful for a pathogen to effectively spread from local lesions, such as the genital tract in this case, to other distinct lymphoid tissue, as observed in pelvic inflammatory disease [42].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…CHO cells deficient in enzymes in the heparan sulfate pathway (PgsA-745, PgsD-677, and CHO-761) (4,36) show decreased infectivity with Chlamydia compared with the parental CHO-K1 line. No reconstitution of chemically mutagenized Chlamydia-resistant CHO cell lines has been reported, presumably because such lines are heavily mutagenized to begin with, complicating identification of the mutations responsible for resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these observations, GAG synthesis by Chlamydia remains controversial, as Taraktchoglou et al (2001) failed to detect chlamydial heparan sulphate-like compounds on some serovars. Moreover, analysis of the completed genomes of C. trachomatis and Chlamydia pneumoniae provided no evidence for chlamydial GAG biosynthesis-related genes (Hackstadt, 1999).…”
Section: Gag Mimicry By Chlamydiamentioning
confidence: 99%